2007
DOI: 10.1103/physrevlett.98.030502
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Entanglement between Gaussian States by Coherent Photon Subtraction

Abstract: We experimentally demonstrate that the entanglement between Gaussian entangled states can be increased by non-Gaussian operations. Coherent subtraction of single photons from Gaussian quadrature-entangled light pulses, created by a nondegenerate parametric amplifier, produces delocalized states with negative Wigner functions and complex structures more entangled than the initial states in terms of negativity. The experimental results are in very good agreement with the theoretical predictions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
284
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(297 citation statements)
references
References 28 publications
(43 reference statements)
9
284
0
4
Order By: Relevance
“…The correlated states produced by our system are suitable to generate mesoscopic single-beam nonclassical states by conditional measurements [20,21]. The conditional measurement is made as follows: the number of detected photons in the idler, m i , is kept only if the number of detected photons in the signal, m s , falls into a specific interval ∆ far from its mean value.…”
Section: Conditional Measurementsmentioning
confidence: 99%
“…The correlated states produced by our system are suitable to generate mesoscopic single-beam nonclassical states by conditional measurements [20,21]. The conditional measurement is made as follows: the number of detected photons in the idler, m i , is kept only if the number of detected photons in the signal, m s , falls into a specific interval ∆ far from its mean value.…”
Section: Conditional Measurementsmentioning
confidence: 99%
“…A simple non-Gaussian operation is the photon subtraction, represented byâ|Ψ whereâ is the bosonic annihilation operator, which can enhance the performance of the Gaussian two-mode entangled state in quantum teleportation [11][12][13] and the densecoding [14]. Entanglement improvement was experimentally realized by a nonlocal photon subtraction [15] and by the local photon subtractions [16], respectively. Furthermore, it was suggested that entanglement distillation can be achieved also by photon addition, represented byâ † |Ψ whereâ † is the bosonic creation operator [17], or by some combinations of addition and subtraction, such as photon-addition-then-subtractionââ † |Ψ and subtraction-then-additionâ †â |Ψ [17], or by coherent combinations of two sequences of photon subtraction and addition [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several implementations of non-Gaussian states have been reported so far, in particular from squeezed light [17][18][19][20][21][22][23][24][25], close-tothreshold parametric oscillators [26,27] in optical cavities [28], and in superconducting circuits [29]. Non-Gaussian operations are also interesting for tasks such as entanglement distillation [30,31] and noiseless amplification [32,33], which are also obtained in a conditional fashion, accepting only those events heralded by a measurement result.…”
Section: Introduction and Definitionsmentioning
confidence: 99%